Time-Dependent Changes in Morphostructural Properties and Relative Abundances of Contributors in Pleurotus ostreatus/Pseudomonas alcaliphila Mixed Biofilms - Crognale, Silvia; Stazi, Silvia Rita; Firrincieli, Andrea; Pesciaroli, Lorena; Fedi, Stefano; Petruccioli, Maurizio; D’Annibale, Alessandro (Frontiers in Microbiology, 2019)
Pleurotus ostreatus dual biofilms with bacteria are known to be involved in rock phosphate solubilization, endophytic colonization and even in nitrogen fixation. Despite these relevant implications, no information is currently available on the architecture of P. ostreatus-based dual biofilms. In addition to this, there is a limited amount of information regarding the estimation of the temporal changes in the relative abundances of the partners in such binary systems. To address these issues, a dual biofilm model system with this fungus was prepared by using Pseudomonas alcaliphila 34 as the bacterial partner due to its very fast biofilm-forming ability. The application of the bacterial inoculum to already settled fungal biofilm on a polystyrene surface coated with hydroxyapatite was the most efficient approach to the production of the mixed system the ultrastructure of which was investigated by a multi-microscopy approach. Transmission electron microscopy analysis showed that the adhesion of bacterial cells onto the mycelial cell wall appeared to be mediated by the presence of an abundant layer of extracellular matrix (ECM). Scanning electron microscopy analysis showed that ECM filaments of bacterial origin formed initially a reticular structure that assumed a tabular semblance after 72 h, thus overshadowing the underlying mycelial network. Across the thickness of the mixed biofilms, the presence of an extensive network of channels with large aggregates of viable bacteria located on the edges of their lumina was found by confocal laser scanning microscopy; on the outermost biofilm layer, a significant fraction of dead bacterial cells was evident. Albeit with tangible differences, similar results regarding the estimation of the temporal shifts in the relative abundances of the two partners were obtained by two independent methods, the former relying on qPCR targeting of 16S and 18S rRNA genes and the latter on ester-linked fatty acid methyl esters analysis